Technology of providing functional safety of information systems at the stage of modernization - Юдін, О. К.; Стрельбіцький, М. А. (Science-based technologies, 2017)
The article analyzes the existing approaches to ensuring the functional security of information systems. The relationship between the compliance with the functional criteria of the information resource and the functional security of the integrated information system of the border authority as a whole is determined. The contradiction between the existing theoretical basis for the provision of functional security and the need for the continuous modernization of information systems as part of an integrated information system is shown. The technology for ensuring the functional security of information systems at the stage of modernization is developed and its main stages are described. Reasonable modernization strategies depend on the importance of the normative level of functional security and the peculiarities of the functioning of the information system. Recommendations on choosing modernization strategies according to the peculiarities of the functioning of the information system are described. The influence of normative values ​​of the observance of the properties of information in the investigation of the probability of a violation of the functioning of the functional security system is determined.